Technical Processing of documentary programs in satellite channels - HUSSEIN, AHMED ABDULSATTAR (ALBAHITH ALALAMI, 2020)
The current research dealt with the study and analysis of the documentaryprogram on RT satellite channel dealt with research in a problem identifiedby the researcher in a major question, which is the methods of technicalprocessing of documentary programs in satellite channels? The goal ofidentifying the channel's handling of its documentary programs.The research is considered descriptive research in which the researcherused the survey method, the content analysis method to analyze (12)documentary programs, It was determined by the comprehensive inventorymethod within the temporal field of research extending from 1/10/2019 to29/12/2019.The researcher has obtained several results, the most important of whichare:* The results showed RT channel is adopting in its Processing of documentaryprograms in the form of film programs, among other forms of programs.* The diversity of the use of photocopying documents in RT channel handlingof its documentary programs, but the focus was more on video animation.